Detectable SARS-CoV-2 specific immune responses in recovered unvaccinated individuals 250 days post wild type infection - Nikolas Weigl; Claire Pleimelding; Leonard Gilberg; Duc Huynh; Isabel Brand; Jan Bruger; Jonathan Frese; Tabea M. Eser; Mohamed I. M. Ahmed; Jessica M. Guggenbuehl-Noller; Renate Stirner; Michael Hoelscher; et al. (PLoS ONE, 2025)
Memory T cells play an important role in mediating long-lasting adaptive immune responses to viral infections, such as SARS-CoV-2. In the context of the latter, much of our current knowledge stems from studies in vaccinated individuals or repeatedly infected individuals. However, limited knowledge is available on these responses in fully naive individuals in German communities. We performed immunophenotyping of a previously naive SARS-CoV-2 cohort in convalescent individuals after asymptomatic to moderate COVID-19. The samples were collected median 250 days post infection during the first wave of the COVID pandemic in Germany (March – May 2020). In this cohort of 174 individuals, we phenotyped different leukocyte cell populations in peripheral blood (B, T and Natural Killer cells). We then assessed the serostatus against the SARS-CoV-2 antigens Nucleocapsid (N) and Spike subunit (S1) with its receptor binding domain (RBD), as these are important correlates of protection, by testing for presence of immunoglobulin G (IgG) antibodies. We also measured IgG antibody responses against the N antigen of the common cold coronaviruses HCoV-OC43, HCoV-HKU1, HCoV-NL63 and HCoV-229E, to determine possible cross-reactivity. In a subset of the cohort (n = 76), we performed intracellular staining assays (ICS) after stimulation with SARS-CoV-2 and HCoV antigens. Key findings are significant differences in frequency of CD4+ memory T cell populations, notably CD4+ TEM and CD4+ TEMRA cells, between the group of SARS-CoV-2 positive individuals and the control group. These differences correlated with cytokine production (TNFα, IFNγ) after stimulation with SARS-CoV-2 peptides, indicating a specific T cell immune response. In conclusion, a clear memory T cell and humoral response can be detected up to 250 days post mild to moderate COVID-19 disease. Our results underline findings reported by others indicating a lasting cellular immune response even in a population which previously had not been exposed to SARS-CoV-2.